Net neutrality principles and its impact on quality of experience based service differentiation in mobile networks - Luis Martínez; Oscar Álvarez San-Jaime; Jan Markendahl (International Telecommunications Society (ITS), 2015)
The overall goal of the incorporation of QoE in the mobile networks deployment is related to optimizing end-user QoE, while making efficient use of network resources and maintaining a satisfied customer base that guarantees the commercial success of the provider's business model. However, the implementation of a QoE-based approach at the service provision, with the potential deployment of fast lanes for premium users, the prioritization of traffic, or the creation of user's categories, may affect the Net Neutrality principles. This paper presents an analysis of how the net neutrality principles will impact the implementation of QoE-based differentiation in the service provision at technical, business and market levels. We introduce a business model framed in the QoE-based differentiation approach analysing the implications of Net Neutrality in the proposed models.
Keywords: 330; Quality of Experience; Net Neutrality; Mobile Networks